Physical health conditions in young children with profound intellectual and multiple disabilities: The prevalence and associations between these conditions. - Mol‐Bakker, Anouk; Van der Putten, Annette A. J.; Krijnen, Wim P.; Waninge, Aly (Child: Care, Health & Development, 2024)
Background: It is thought that physical health conditions start at a young age in people with profound intellectual and multiple disabilities (PIMD). Knowledge regarding the prevalence, associations and development of these physical health conditions could be used for purposes of prevention as well as appropriate care and support but is currently lacking. Objective: The aim of this study is to gain insight into the prevalence of physical health conditions and associations between these conditions in young children with PIMD. Methods: The study used cross‐sectional data related to the physical health conditions of children with PIMD (n = 51, aged between 12 and 61 months). Data were collected in Belgium and in the Netherlands through a checklist filled in by primary caregiver(s). Physical health conditions were classified into categories by the 10th revision of the International Classification of Diseases and Related Health Problems (ICD‐10) system. The number of physical health conditions and associations between them were analysed. The analysis focused on prevalence rates and associations represented by odds ratios (p < 0.05). A graphical model was estimated to represent dependencies and conditional dependencies between physical health conditions. Results: We found a mean of 3.8 (range 1–8, SD 1.9) physical health conditions per child. Most of the physical health conditions were found in the ICD‐10 chapter 'Nervous System', with hypotonia as the most frequent at 70.6%. Five significant large associations were found between spasticity–contractures (OR 9.54); circulatory system–contractures (OR 7.50); scoliosis–contractures (OR 10.25); hearing impairments–skin problems (OR 58.20) and obstipation–hypotonia (OR 19.98). Conclusion: This study shows that at a young age, multiple physical health conditions are present in children with PIMD. In addition, we found five associations between physical health conditions.